Drink deep : a Chicagoland vampires novel - Neill, Chloe (Neill, Chloe. Chicagoland vampires novel, 2011)
"Clouds are brewing over Cadogan House, and recently turned vampire Merit can't tell if this is the darkness before the dawn or the calm before the storm. With the city in turmoil over paranormals and the state threatening to pass a paranormal registration act, times haven't been this precarious for vampires since they came out of the closet. If only they could lie low for a bit and let the mortals calm down. That's when the waters of Lake Michigan suddenly turn pitch-black--and things really start getting ugly. Chicago's mayor insists it's nothing to worry about, but Merit knows only the darkest magic could have woven a spell powerful enough to change the very fabric of nature. She'll have to turn to friends old and new to find out who's behind this, and stop them before it's too late for vampires and humans alike"--